Preparation method of surface layer metastable active mineral powder and high early strength super-sulfated cement thereof
Patent Information
- Application Number
- CN202611211405.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-08-11
AI Technical Summary
[0005]本发明提供一种表层亚稳型活性矿粉的制备方法及其高早强超硫酸盐水泥,其通过在矿渣粉颗粒表面形成非晶、亚稳态且可转化的钙铝硅矿化前驱体,其能够在水化反应早期重新溶解、重排并转化为水化产物,有效提升了矿渣粉的早期反应活性,克服了超硫酸盐水泥早期强度不足的问题
本发明放弃了在矿渣胶凝组分颗粒表面直接生成稳定晶种的方式,而是在矿渣胶凝组分颗粒表面形成非晶、亚稳态且可转化以及非连续的钙铝硅矿化前驱体,不仅避免了外掺晶种容易团聚、表面晶种过度长大和连续包覆阻碍矿渣后续溶解等问题,而且在超硫酸盐水泥的水化早期所述前驱层转化为AFt和C-(A)-S-H等水化胶凝产物,有效提升了超硫酸盐水泥的早期强度。为此,本发明先利用钙源、铝源、硅源和非晶稳相组分形成的非晶稳相型钙铝硅前驱液对矿渣胶凝组分颗粒表面进行改性处理,在此过程中,所述非晶稳相型钙铝硅前驱液在矿渣胶凝组分颗粒表面形成半干微水膜,所述矿渣胶凝组分颗粒表层在该微水膜中发生轻度选择性溶蚀,释放少量自源Si、Al、Ca组分,其和所述前驱液提供的Ca、Al、Si组分共同在颗粒表面发生局部富集、短程聚集、结晶,而不是在体相溶液中随机沉淀。同时,利用所述非晶稳相组分的羧基、羟基、膦酸基或氨基与Ca2+、铝氧基团、硅氧低聚体进行动态配位,抑制上述的Ca、Al、Si组分形成长程有序晶体,使其以无定形或低有序度矿化前驱体形式暂时保留于矿渣胶凝组分颗粒表面。而且,由于上述反应发生在半干微水膜中,体系缺乏晶体充分迁移、生长和长大的环境,因而能够避免传统湿法沉淀或表面晶种化过程中的体相沉淀、晶种团聚和连续包覆问题。在超硫酸盐水泥中的所述硫酸盐和碱性调控组分提供的SO42-、OH-和Ca2+作用下促使所述非晶钙铝硅矿化前驱体进行再水化、重新溶解、离子重排和矿化转化,快速生成AFt、钙铝硫类水化前驱体和C-(A)-S-H类凝胶,该过程使早期水化产物优先在矿渣胶凝组分颗粒表面形成,从而加快早期刚性骨架搭建。由此,本发明将传统超硫酸盐水泥的早期水化过程由孔溶液中的随机形成转变为所述矿化前驱体的触发转化和定域生长,使水化反应快速启动,有效缩短了水化反应过程,提高了早期强度,并保持后期水化持续发展。进一步地,本发明将经过上述非晶稳相型钙铝硅前驱液处理的矿渣胶凝组分与含有活性二氧化硅的干粉反应后再与水泥熟料粉、石膏粉共同反应,从而形成本发明的表层亚稳型活性矿粉,将其作为超硫酸盐水泥的胶凝组分时,水泥熟料粉和石膏粉分别释放活性钙铝组分和硫酸根离子,并与预处理胶凝组分发生协同溶解、离子重排和矿化转化,促进AFt和C-(A)-S-H类水化产物在矿渣胶凝组分表面快速、定域生成,从而加快颗粒间胶结网络和早期承载骨架的形成,提升超硫酸盐水泥的早期强度。
Smart Images

Figure CN122705196B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cement-based building materials, specifically to a method for preparing a surface metastable active mineral powder and its high early strength supersulfate cement. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Traditional supersulfate cement uses granulated blast furnace slag powder (hereinafter referred to as slag powder) as the main cementitious component. However, its glassy structure dissolves slowly at room temperature. Early hydration usually relies on the addition of a small amount of alkaline components to increase the alkalinity of the pore solution, which then gradually promotes the deagglomeration of the slag powder surface and releases active ions such as Ca, Si, and Al. Due to insufficient supply of reactive ions in the early stage, hydration products tend to form randomly in the pore solution, making it difficult to quickly establish a continuous load-bearing structure on the surface of the slag powder particles. This results in problems such as long setting time, significant induction period, and low 1-day and 3-day strength.
[0004] To improve the early performance of supersulfate cement, current methods typically include increasing the dosage of alkaline activators, increasing the dosage of silicate or aluminate clinker, adding external early-strength agents or nanocrystals, and inducing nucleation on the surface of mineral powder. While these methods can promote early hydration to some extent, they still have the following shortcomings: First, simply increasing the dosage of clinker or alkaline activators weakens the advantages of supersulfate cement in terms of low clinker content, low carbon content, and durability. Second, externally added seed crystals are prone to agglomeration and do not have sufficient contact with the surface of granulated blast furnace slag powder particles, thus limiting their effectiveness. Third, directly generating seed crystals on the surface of slag powder particles prematurely consumes the reactivity of the slag powder; if a continuous coating layer is formed, it may also hinder the subsequent dissolution of the slag powder, thereby affecting the development of early strength. Fourth, the core of existing surface nucleation or seeding methods is usually still to provide nucleation sites, which cannot fundamentally solve the contradiction between "the need for rapid transformation of reaction units in the early stage" and "the inability to crystallize and grow prematurely during the pretreatment stage." Summary of the Invention
[0005] This invention provides a method for preparing a metastable active mineral powder with a surface layer and a high early-strength hypersulfate cement thereof. By forming an amorphous, metastable, and convertible calcium-aluminum-silica mineralization precursor on the surface of slag powder particles, this precursor can redissolve, rearrange, and transform into hydration products in the early stages of the hydration reaction, effectively improving the early-stage reactivity of the slag powder and overcoming the problem of insufficient early-stage strength in hypersulfate cement. Specifically, the technical solution of this invention is as follows.
[0006] In a first aspect, the present invention provides a method for preparing a surface metastable active mineral powder, comprising the following steps: (1) An amorphous stable calcium aluminum silicon precursor solution is sprayed into the slag cementitious component in motion for mixing treatment, and then dry powder containing active silica is added for mixing reaction to obtain the pretreated cementitious component. The amorphous stable calcium aluminum silicon precursor solution includes: calcium source, aluminum source, silicon source, amorphous stable component and water, and the amorphous stable component includes at least one of: polyaspartate, polyacrylate, carboxymethyl chitosan and gluconate.
[0007] (2) The pretreated cementitious component is mixed with cement clinker powder and gypsum powder and reacted. After the reaction is completed, it is dried to obtain the surface metastable active mineral powder.
[0008] Further, in step (1), the slag cementing component includes any one of granulated blast furnace slag powder, granulated blast furnace slag powder and industrial solid waste micro powder. Optionally, the industrial solid waste micro powder accounts for 5-40% of the mass of the slag cementing component.
[0009] Furthermore, the industrial solid waste powder includes at least one of the following: steel slag powder, nickel-iron slag powder, and phosphorus slag powder.
[0010] Furthermore, in step (1), the fineness of the slag cementitious component is 300~500 mesh.
[0011] Further, in step (1), the amorphous stable calcium aluminum silicon precursor liquid is 2 to 8% of the mass of the slag cementing component.
[0012] Further, in step (1), in the amorphous stable calcium-aluminum-silicon precursor solution: the calcium source provides Ca 2+ The concentration is 0.15~1 mol / L, and the Ca / (Si+Al) molar ratio is 0.5~2.5:1, the Si / Al molar ratio is 0.5~6:1, and the concentration of the amorphous stable phase component is 0.2~1 mol / L.
[0013] Further, in step (1), the calcium source includes at least one of calcium formate, calcium acetate, calcium lactate, and carbide slag leachate.
[0014] Further, in step (1), the aluminum source includes at least one of aluminate, aluminum sol, etc. Optionally, the mass fraction of aluminum oxide in the aluminum sol is 5-20%.
[0015] Further, in step (1), the silicon source includes at least one of silica sol and nano-silica dispersion. Optionally, the mass fraction of silica in the silica sol and nano-silica dispersion is 15-30%.
[0016] Furthermore, in step (1), the mixing process takes 3 to 20 minutes.
[0017] Further, in step (1), the dry powder is 1.5 to 2.5% of the mass of the slag cementitious component.
[0018] Further, in step (1), the dry powder includes at least one of nano-silica, silica fume, etc.
[0019] Furthermore, in step (1), the mixing reaction time is 10-15 min.
[0020] Further, in step (2), the ratio of the pretreated cementitious component, cement clinker powder, and gypsum powder is 100 parts by weight: 3~4 parts by weight: 2.8~3.5 parts by weight.
[0021] Further, in step (2), the cement clinker powder includes at least one of sulfoaluminate cement, aluminate cement, etc.
[0022] Further, in step (2), the gypsum powder includes at least one of the following: natural gypsum powder, desulfurized gypsum powder, phosphogypsum powder, fluorogypsum powder, etc.
[0023] Furthermore, in step (2), the reaction time is 15-20 min.
[0024] Furthermore, in step (2), the drying temperature is 35~45℃, and the material is dried until the moisture content is not higher than 0.5%.
[0025] Secondly, the present invention provides a high early strength supersulfate cement comprising the following components in the following proportions: 45-80 parts by weight of the above-mentioned surface metastable active mineral powder of the present invention, 15-45 parts by weight of sulfate, 1-8 parts by weight of calcium-silicon phase continuous activation component, and 0.5-5 parts by weight of alkaline regulating component.
[0026] Furthermore, the sulfate includes at least one of the following: desulfurized gypsum, phosphogypsum, titanium gypsum, natural gypsum, hemihydrate gypsum, anhydrite, etc.
[0027] Furthermore, the calcium-silicon phase continuously activated component includes at least one of the following: silicate clinker powder, steel slag powder, and recycled waste concrete powder. The calcium-silicon phase continuously activated component is used to continuously release Ca during the hydration process. 2+ and OH - This maintains the alkaline environment required for the depolymerization of the metastable active mineral powder on the surface during the hydration reaction.
[0028] Furthermore, the alkaline regulating component includes at least one of the following: calcium carbide slag powder, quicklime, steel slag powder, calcium oxide powder, and calcium hydroxide powder. The alkaline regulating component is not primarily intended for rapid activation by a strong alkali, but rather for adjusting the early pH and Ca content of the system. 2+ The supply concentration allows the amorphous precursor layer on the surface of the metastable active mineral powder to undergo continuous mineralization transformation, promoting the continuous generation of hydration products.
[0029] Furthermore, the high early strength supersulfate cement also includes at least one of the functional admixtures such as water-reducing agent, water-retaining agent, setting regulator, defoamer, and dispersant.
[0030] Compared with the prior art, the present invention has at least the following beneficial technical effects: This invention abandons the method of directly generating stable seed crystals on the surface of slag cementitious component particles. Instead, it forms an amorphous, metastable, convertible, and discontinuous calcium aluminum silicate mineralization precursor on the surface of slag cementitious component particles. This not only avoids problems such as easy agglomeration of externally added seed crystals, excessive growth of surface seed crystals, and continuous coating hindering the subsequent dissolution of slag, but also transforms the precursor layer into hydration cementitious products such as AFt and C-(A)-SH in the early stage of hydration of supersulfate cement, effectively improving the early strength of supersulfate cement. Therefore, this invention first uses an amorphous stable-phase calcium-aluminum-silicon precursor solution formed from calcium, aluminum, silicon, and amorphous stable phase components to modify the surface of slag cementitious component particles. During this process, the amorphous stable-phase calcium-aluminum-silicon precursor solution forms a semi-dry micro-water film on the surface of the slag cementitious component particles. The surface of the slag cementitious component particles undergoes mild selective dissolution within this micro-water film, releasing a small amount of self-sourced Si, Al, and Ca components. These components, along with the Ca, Al, and Si components provided by the precursor solution, undergo local enrichment, short-range aggregation, and crystallization on the particle surface, rather than random precipitation in the bulk solution. Simultaneously, the carboxyl, hydroxyl, phosphonic acid, or amino groups of the amorphous stable phase component are utilized in conjunction with Ca... 2+ The aluminooxy groups and silicon-oxygen oligomers dynamically coordinate to inhibit the formation of long-range ordered crystals in the aforementioned Ca, Al, and Si components, allowing them to temporarily remain on the surface of the slag cementitious component particles in the form of amorphous or low-order mineralization precursors. Furthermore, since the above reaction occurs in a semi-dry micro-water film, the system lacks an environment conducive to sufficient crystal migration, growth, and maturation, thus avoiding the problems of bulk precipitation, seed agglomeration, and continuous coating encountered in traditional wet precipitation or surface seeding processes. The sulfate and alkaline regulating components in the supersulfate cement provide SO4. 2- OH - and Ca 2+Under the influence of this process, the amorphous calcium-aluminum-silicon mineralization precursor undergoes rehydration, redissolution, ion rearrangement, and mineralization transformation, rapidly generating AFt, calcium-aluminum-sulfur hydration precursors, and C-(A)-SH gels. This process preferentially forms early hydration products on the surface of slag cementitious particles, thereby accelerating the early rigid framework construction. Therefore, this invention transforms the early hydration process of traditional supersulfate cement from random formation in pore solutions to triggered transformation and localized growth of the mineralization precursors, enabling rapid initiation of the hydration reaction, effectively shortening the hydration process, improving early strength, and maintaining continuous development of later hydration. Furthermore, in this invention, the slag cementitious component treated with the above-mentioned amorphous stable calcium aluminum silica precursor liquid reacts with dry powder containing active silica, and then reacts with cement clinker powder and gypsum powder to form the surface metastable active mineral powder of this invention. When used as the cementitious component of supersulfate cement, the cement clinker powder and gypsum powder release active calcium aluminum components and sulfate ions respectively, and undergo synergistic dissolution, ion rearrangement and mineralization transformation with the pretreated cementitious component, promoting the rapid and localized generation of AFt and C-(A)-SH hydration products on the surface of the slag cementitious component, thereby accelerating the formation of interparticle cementitious network and early load-bearing skeleton, and improving the early strength of supersulfate cement. Attached Figure Description
[0031] The accompanying drawings, which form part of this specification, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Hereinafter, embodiments of the invention will be described in detail with reference to the accompanying drawings, wherein: Figure 1 The image shows a surface metastable active mineral powder sample prepared in Example 1 below.
[0032] Figure 2 The image shows a surface metastable active mineral powder sample prepared in Example 2 below.
[0033] Figure 3 The image shows a surface metastable active mineral powder sample prepared in Example 3 below.
[0034] Figure 4 The image shows a surface metastable active mineral powder sample prepared in Example 5 below.
[0035] Figure 5 The image shows a surface metastable active mineral powder sample prepared in Example 6 below.
[0036] Figure 6 The image shows a surface metastable active mineral powder sample prepared in Example 7 below.
[0037] Figure 7 The image shows a surface metastable active mineral powder sample prepared in Example 8 below. Detailed Implementation
[0038] The present invention is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention.
[0040] Example 1 1. A method for preparing a surface metastable active mineral powder, comprising the following steps: (1) Calcium formate, sodium aluminate, nano-silica dispersion (where the mass fraction of silica is 15%), amorphous stable phase component (sodium polyaspartate), and water are mixed and stirred until homogeneous to obtain an amorphous stable phase calcium-aluminum-silica precursor solution for later use. Wherein: the calcium formate provides Ca... 2+ The concentration of the amorphous stable phase component is 0.75 mol / L, the Ca / (Si+Al) molar ratio is 1.5, the Si / Al molar ratio is 4:1, and the concentration of the amorphous stable phase component is 0.5 mol / L.
[0041] (2) The slag cementing component (granulated blast furnace slag powder with a fineness of 450 mesh) is added to a high-speed mixer and stirred at a rate of 500 r / min. The atomized amorphous stable calcium aluminum silicon precursor liquid of this embodiment is sprayed into the mixer, and the precursor liquid is 5% of the mass of the slag cementing component. After spraying, stirring is continued for 10 min for mixing treatment. Then, 2% of the mass of the slag cementing component of nano silica dry powder is added and stirred for 10 min for mixing reaction to obtain the pretreated cementing component.
[0042] (3) The pretreated cementitious component is mixed with sulfoaluminate cement and desulfurized gypsum powder in a ratio of 100 parts by weight: 3.4 parts by weight: 3 parts by weight, and stirred for 15 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 40°C and dried to a moisture content of 0.3% to obtain the surface metastable active mineral powder (e.g. Figure 1 (As shown).
[0043] 2. A method for preparing high early strength supersulfate cement, comprising the following steps: (1) Weigh the following components in the following proportions: 60 parts by weight of surface metastable active mineral powder, 25 parts by weight of desulfurized gypsum, 4 parts by weight of ordinary silicate clinker powder, and 2 parts by weight of calcium oxide powder. Mix the above components and stir for 2 minutes. Then add 40.9 parts by weight of water and stir at a rate of 500 r / min for 120 seconds. Stop for 15 seconds and then stir at a rate of 1000 r / min for 120 seconds to obtain supersulfate cement.
[0044] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested. The compressive strength was tested according to "GB / T 17671-2021". The test results of each property are shown in Table 1 below.
[0045] Table 1
[0046] Example 2 1. A method for preparing a surface metastable active mineral powder, comprising the following steps: (1) Calcium acetate, aluminum sol (with alumina mass fraction of 5%), nano-silica dispersion (with silica mass fraction of 15%), amorphous stable phase component (carboxymethyl chitosan), and water are mixed and stirred until homogeneous to obtain an amorphous stable phase calcium-aluminum-silica precursor solution for later use. Wherein: the calcium acetate provides Ca... 2+ The concentration of the amorphous stable phase component is 1 mol / L, and the Ca / (Si+Al) molar ratio is 2.5, the Si / Al molar ratio is 0.5:1, and the concentration of the amorphous stable phase component is 1.0 mol / L.
[0047] (2) The slag cementing component (granulated blast furnace slag powder with a fineness of 300 mesh) is added to a high-speed mixer and stirred at a rate of 500 r / min. The atomized amorphous stable calcium aluminum silicon precursor liquid of this embodiment is sprayed into the mixer, and the precursor liquid accounts for 8% of the mass of the slag cementing component. After spraying, stirring is continued for 20 min for mixing treatment. Then, 2.5% of the mass of the slag cementing component of nano silica dry powder is added and stirred for 15 min for mixing reaction to obtain the pretreated cementing component.
[0048] (3) The pretreated cementitious component is mixed with sulfoaluminate cement and phosphogypsum powder in a ratio of 100 parts by weight: 4 parts by weight: 3.5 parts by weight, and stirred for 15 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 45°C and dried to a moisture content of 0.2% to obtain the surface metastable active mineral powder (e.g. Figure 2 (As shown).
[0049] 2. A method for preparing high early strength supersulfate cement, comprising the following steps: (1) Weigh the following components in the following proportions: 80 parts by weight of surface metastable active mineral powder, 45 parts by weight of phosphogypsum, 8 parts by weight of recycled waste concrete powder, and 5 parts by weight of carbide slag powder. Mix the above components and stir for 2 minutes. Then add 62 parts by weight of clean water and stir at a rate of 500 r / min for 120 seconds. Stop for 15 seconds and then stir at a rate of 1000 r / min for 120 seconds to obtain supersulfate cement.
[0050] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 2 below.
[0051] Table 2
[0052] Example 3 1. A method for preparing a surface metastable active mineral powder, comprising the following steps: (1) Calcium lactate, aluminum sol (of which the mass fraction of alumina is 20%), silica sol (of which the mass fraction of nano-silica is 30%), and amorphous stable phase component (sodium polyacrylate) are mixed with water and stirred until homogeneous to obtain an amorphous stable phase calcium-aluminum-silicon precursor solution for later use. Wherein: the calcium lactate provides Ca... 2+ The concentration of the amorphous stable phase component is 0.15 mol / L, the Ca / (Si+Al) molar ratio is 0.5, the Si / Al molar ratio is 6:1, and the concentration of the amorphous stable phase component is 0.2 mol / L.
[0053] (2) The slag cementing component (composed of granulated blast furnace slag powder with a fineness of 500 mesh and steel slag micro powder, wherein the mass percentage of the steel slag micro powder is 40%) is added to a high-speed mixer and stirred at a rate of 800 r / min. Atomized amorphous stable calcium aluminum silicon precursor liquid of this embodiment is sprayed into the mixer, wherein the precursor liquid is 2% of the mass of the slag cementing component. After spraying, stirring is continued for 3 min for mixing treatment. Then, 1.5% of the mass of the slag cementing component and silica fume are added and stirred for 10 min for mixing reaction to obtain the pretreated cementing component.
[0054] (3) The pretreated cementitious component is mixed with aluminate cement and natural gypsum powder in a ratio of 100 parts by weight: 3 parts by weight: 2.8 parts by weight, and stirred for 20 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 35°C and dried to a moisture content of 0.5% to obtain the surface metastable active mineral powder (e.g. Figure 3 (As shown).
[0055] 2. A method for preparing high early strength supersulfate cement, comprising the following steps: (1) Weigh the following components in the following proportions: 45 parts by weight of surface metastable active mineral powder, 15 parts by weight of phosphogypsum, 1 part by weight of ordinary silicate clinker powder, and 0.5 parts by weight of calcium hydroxide powder. Mix the above components and stir for 2 minutes. Then add 27.5 parts by weight of water and stir at a rate of 500 r / min for 120 seconds. Stop for 15 seconds and then stir at a rate of 1000 r / min for 120 seconds to obtain supersulfate cement.
[0056] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 3 below.
[0057] Table 3
[0058] Example 4 A method for preparing high early strength supersulfate cement includes the following steps: (1) Weigh the following components in the following proportions: 60 parts by weight of granulated blast furnace slag powder with a fineness of 450 mesh, 25 parts by weight of desulfurized gypsum, 4 parts by weight of ordinary silicate clinker powder, and 2 parts by weight of calcium oxide powder.
[0059] (2) Mix the above components and stir for 2 minutes. Then add 40.9 parts by weight of clean water and stir at a rate of 500 r / min for 120 s. Stop for 15 s and then stir at a rate of 1000 r / min for 120 s to obtain supersulfate cement.
[0060] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 4 below.
[0061] Table 4
[0062] Example 5 A method for preparing high early strength supersulfate cement is the same as in Example 1 above, except that the metastable active mineral powder for the surface layer in this example is prepared by the following method: (1) Calcium formate, sodium aluminate, and nano-silica dispersion (where the mass fraction of silica is 15%) are mixed with water and stirred until homogeneous to obtain an aluminum-silica precursor solution for later use. Wherein: the calcium formate provides Ca... 2+ The concentration was 0.75 mol / L, and the Ca / (Si+Al) molar ratio was 1.5, while the Si / Al molar ratio was 4:1.
[0063] (2) The slag cementing component (granulated blast furnace slag powder with a fineness of 450 mesh) is added to a high-speed mixer and stirred at a rate of 500 r / min. The atomized aluminum-silicon precursor liquid of this embodiment is sprayed into the mixer, and the precursor liquid is 5% of the mass of the slag cementing component. After spraying, stirring is continued for 10 min for mixing treatment. Then, 2% of the mass of the slag cementing component of nano-silica dry powder is added and stirred for 10 min for mixing reaction to obtain the pretreated cementing component.
[0064] (3) The pretreated cementitious component is mixed with sulfoaluminate cement and desulfurized gypsum powder in a ratio of 100 parts by weight: 3.4 parts by weight: 3 parts by weight, and stirred for 15 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 40°C and dried to a moisture content of 0.3% to obtain the surface metastable active mineral powder (e.g. Figure 4 (As shown).
[0065] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 5 below.
[0066] Table 5
[0067] Example 6 A method for preparing high early strength supersulfate cement is the same as in Example 2 above, except that the metastable active mineral powder for the surface layer in this example is prepared by the following method: (1) The amorphous stable phase component (carboxymethyl chitosan) is mixed with water and stirred evenly to obtain a precursor solution for later use. The concentration of the amorphous stable phase component is 1.0 mol / L.
[0068] (2) The slag cementing component (granulated blast furnace slag powder with a fineness of 300 mesh) is added to a high-speed mixer and stirred at a rate of 500 r / min. The precursor liquid described in this embodiment is sprayed into the mixer, and the precursor liquid accounts for 8% of the mass of the slag cementing component. After spraying, stirring is continued for 20 min for mixing treatment. Then, 2.5% of the mass of the slag cementing component of nano-silica dry powder is added and stirred for 15 min for mixing reaction to obtain the pretreated cementing component.
[0069] (3) The pretreated cementitious component is mixed with sulfoaluminate cement and phosphogypsum powder in a ratio of 100 parts by weight: 4 parts by weight: 3.5 parts by weight, and stirred for 15 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 45°C and dried to a moisture content of 0.2% to obtain the surface metastable active mineral powder (e.g. Figure 5 (As shown).
[0070] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 6 below.
[0071] Table 6
[0072] Example 7 A method for preparing high early strength supersulfate cement is the same as in Example 2 above, except that the metastable active mineral powder for the surface layer in this example is prepared by the following method: (1) Calcium acetate, aluminum sol (with alumina mass fraction of 5%), nano-silica dispersion (with silica mass fraction of 15%), amorphous stable phase component (carboxymethyl chitosan), and water are mixed and stirred until homogeneous to obtain an amorphous stable phase calcium-aluminum-silica precursor solution for later use. Wherein: the calcium acetate provides Ca... 2+ The concentration of the amorphous stable phase component is 1 mol / L, and the Ca / (Si+Al) molar ratio is 2.5, the Si / Al molar ratio is 0.5:1, and the concentration of the amorphous stable phase component is 1.0 mol / L. Then, the amorphous stable calcium aluminum silicon precursor solution is dried to remove moisture, yielding amorphous stable calcium aluminum silicon precursor powder.
[0073] (2) The slag cementing component (granulated blast furnace slag powder with a fineness of 300 mesh) is added to a high-speed mixer and stirred at a rate of 500 r / min. The amorphous stable calcium aluminum silicon precursor powder described in this embodiment is added to the mixture at an amount of 8% of the mass of the slag cementing component. After spraying, stirring is continued for 20 min for mixing treatment. Then, 2.5% of the mass of the slag cementing component of nano silica dry powder is added and stirred for 15 min for mixing reaction to obtain the pretreated cementing component.
[0074] (3) The pretreated cementitious component is mixed with sulfoaluminate cement and phosphogypsum powder in a ratio of 100 parts by weight: 4 parts by weight: 3.5 parts by weight, and stirred for 15 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 45°C and dried to a moisture content of 0.2% to obtain the surface metastable active mineral powder (e.g. Figure 6 (As shown).
[0075] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 7 below.
[0076] Table 7
[0077] Example 8 A method for preparing high early strength supersulfate cement is the same as in Example 3 above, except that the metastable active mineral powder for the surface layer in this example is prepared by the following method: (1) Calcium lactate, aluminum sol (of which the mass fraction of alumina is 20%), silica sol (of which the mass fraction of nano-silica is 30%), and amorphous stable phase component (sodium polyacrylate) are mixed with water and stirred until homogeneous to obtain an amorphous stable phase calcium-aluminum-silicon precursor solution for later use. Wherein: the calcium lactate provides Ca... 2+ The concentration of the amorphous stable phase component is 0.15 mol / L, the Ca / (Si+Al) molar ratio is 0.5, the Si / Al molar ratio is 6:1, and the concentration of the amorphous stable phase component is 0.2 mol / L.
[0078] (2) The slag cementitious component (composed of granulated blast furnace slag powder with a fineness of 500 mesh and steel slag micro powder, wherein the mass percentage of the steel slag micro powder is 40%) is added to a high-speed mixer and stirred at a rate of 800 r / min. Atomized amorphous stable calcium aluminum silicon precursor liquid of this embodiment is sprayed into the mixer, wherein the precursor liquid accounts for 2% of the mass of the slag cementitious component. After spraying, stirring is continued for 3 min for mixing treatment to obtain the pretreated cementitious component.
[0079] (3) The pretreated cementitious component is mixed with aluminate cement and natural gypsum powder in a ratio of 100 parts by weight: 3 parts by weight: 2.8 parts by weight, and stirred for 20 minutes to carry out the mixing reaction. After the reaction is completed, it is heated to 35°C and dried to a moisture content of 0.5% to obtain the surface metastable active mineral powder (e.g. Figure 7 (As shown).
[0080] Performance testing: The setting time and compressive strength of the supersulfate cement prepared in this embodiment were tested using the same method as in Example 1 above. The test results of each property are shown in Table 8 below.
[0081] Table 8
[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a surface metastable active mineral powder, characterized in that, Includes the following steps: (1) Amorphous stable calcium aluminum silicon precursor liquid was sprayed into the slag cementitious component in motion for mixing treatment, and then dry powder containing active silica was added for mixing reaction to obtain pretreated cementitious component. The amorphous stable calcium-aluminum-silicon precursor solution comprises: a calcium source, an aluminum source, a silicon source, an amorphous stable component, and water. The amorphous stable component comprises at least one of: polyaspartate, polyacrylate, carboxymethyl chitosan, and gluconate. The amorphous stable calcium-aluminum-silicon precursor solution accounts for 2-8% of the mass of the slag cementitious component. In the amorphous stable calcium-aluminum-silicon precursor solution, the calcium source provides Ca... 2+ The concentration is 0.15~1 mol / L, and the Ca / (Si+Al) molar ratio is 0.5~2.5:1, and the Si / Al molar ratio is 0.5~6:1; the concentration of the amorphous stable phase component in the amorphous stable phase calcium aluminum silicon precursor solution is 0.2~1 mol / L; the dry powder containing active silica is 1.5~2.5% of the mass of the slag cementing component; (2) The pretreated cementitious component is mixed with cement clinker powder and gypsum powder in a ratio of 100 parts by weight: 3-4 parts by weight: 2.8-3.5 parts by weight and then reacted. After the reaction is completed, the mixture is dried to obtain the surface metastable active mineral powder. The cement clinker powder includes at least one of sulfoaluminate cement and aluminate cement.
2. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the slag cementing component includes any one of granulated blast furnace slag powder, granulated blast furnace slag powder and industrial solid waste micro powder.
3. The method for preparing surface metastable active mineral powder according to claim 2, characterized in that, In step (1), the industrial solid waste powder accounts for 5 to 40% of the mass of the slag cementitious component.
4. The method for preparing surface metastable active mineral powder according to claim 2, characterized in that, The industrial solid waste powder includes at least one of the following: steel slag powder, nickel-iron slag powder, and phosphorus slag powder.
5. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the calcium source includes at least one of calcium formate, calcium acetate, calcium lactate, and carbide slag leachate.
6. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the aluminum source includes at least one of aluminate and aluminum sol.
7. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the silicon source includes at least one of silica sol and nano silica dispersion.
8. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the mixing process takes 3 to 20 minutes.
9. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the dry powder containing active silica includes at least one of nano silica and silica ash.
10. The method for preparing surface metastable active mineral powder according to claim 1, characterized in that, In step (1), the mixing reaction takes 10 to 15 minutes.
11. The method for preparing surface metastable active mineral powder according to any one of claims 1-10, characterized in that, In step (2), the gypsum powder includes at least one of the following: natural gypsum powder, desulfurized gypsum powder, phosphogypsum powder, and fluorogypsum powder.
12. The method for preparing surface metastable active mineral powder according to any one of claims 1-10, characterized in that, In step (2), the reaction time is 15-20 min.
13. The method for preparing surface metastable active mineral powder according to any one of claims 1-10, characterized in that, In step (2), the drying temperature is 35~45℃, and the material is dried until the moisture content is not higher than 0.5%.
14. A high early-strength supersulfate cement, characterized in that, The product comprises the following components in the following proportions: 45-80 parts by weight of surface metastable active mineral powder obtained by the preparation method according to any one of claims 1-13, 15-45 parts by weight of sulfate, 1-8 parts by weight of calcium-silicon phase continuously activated component, and 0.5-5 parts by weight of alkaline regulating component; wherein the calcium-silicon phase continuously activated component includes at least one of steel slag powder and waste concrete recycled micro powder.
15. The high early-strength supersulfate cement according to claim 14, characterized in that, The sulfates include at least one of the following: desulfurized gypsum, phosphogypsum, titanium gypsum, natural gypsum, hemihydrate gypsum, and anhydrite.
16. The high early-strength supersulfate cement according to claim 14, characterized in that, The alkaline regulating component includes at least one of the following: calcium carbide slag powder, quicklime, steel slag powder, calcium oxide powder, and calcium hydroxide powder.
17. The high early-strength supersulfate cement according to claim 14, characterized in that, It also includes at least one of the following: water-reducing agent, water-retaining agent, setting regulator, defoamer, and dispersant.
Citation Information
Patent Citations
Modified blast furnace slag material and preparation technology thereof
CN107793061A
Blast furnace slag cement synthetic method and blast furnace slag cement produced by this method
KR1020110053833A